2022
DOI: 10.1186/s13395-022-00287-8
|View full text |Cite
|
Sign up to set email alerts
|

Meeting report: the 2021 FSHD International Research Congress

Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is the second most common genetic myopathy, characterized by slowly progressing and highly heterogeneous muscle wasting with a typical onset in the late teens/early adulthood [1]. Although the etiology of the disease for both FSHD type 1 and type 2 has been attributed to gain-of-toxic function stemming from aberrant DUX4 expression, the exact pathogenic mechanisms involved in muscle wasting have yet to be elucidated [2–4]. The 2021 FSHD International Research Congr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
0
17
0
3
Order By: Relevance
“…The authors suggested that this lack of benefit was possibly due to the starting of antisense administration after muscle damage had already occurred, or because females were used, in which the disease is considered more severe. However, using the same mouse model but with continual TMX-mediated DUX4 expression, we [ 33 , 34 ] and others [ 35 ] achieved both DUX4 knockdown and amelioration in the muscle/body mass, muscle function and/or muscle histology. In previous studies, we used 16-week-old male mice and inducible DUX4 expression that has been proven to cause more severe pathology than the leaky level, regardless of the animal’s sex [ 36 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The authors suggested that this lack of benefit was possibly due to the starting of antisense administration after muscle damage had already occurred, or because females were used, in which the disease is considered more severe. However, using the same mouse model but with continual TMX-mediated DUX4 expression, we [ 33 , 34 ] and others [ 35 ] achieved both DUX4 knockdown and amelioration in the muscle/body mass, muscle function and/or muscle histology. In previous studies, we used 16-week-old male mice and inducible DUX4 expression that has been proven to cause more severe pathology than the leaky level, regardless of the animal’s sex [ 36 ].…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, as demonstrated here, vivoPMO chemistry with a PMO backbone conjugated with a cell-penetrating octaguanidine dendrimer effectively penetrates the skeletal muscles, though the development of safer systems to improve tissue penetration will be necessary for the translation of antisense therapeutics into the clinic. Alternatively, the PMO-PACS4 sequence could be conjugated with other cell-penetrating peptides, such as Sarepta Therapeutics' PPMO chemistry, which has displayed positive results in a phase 2 clinical trial for Duchenne muscular dystrophy (company's report: https://investorrelations.sarepta.com/news-releases/news-releasedetails/sarepta-therapeutics-reports-positive-clinical-results-phase-2; accessed on 20 May 2022), or with monoclonal antibodies targeting the transferrin receptor to enable muscle delivery, such as those being trialed in FSHD animal models by Avidity Biosciences or Dyne Therapeutics [35]. Moreover, a comparison of the antisense efficiency between different systemic delivery routes should be conducted, for example between the intraperitoneal route used here and the intravenous or subcutaneous delivery that has been used in clinical settings, to obtain the best therapeutic benefit with the highest clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several small molecules that inhibit DUX4 expression have been described, including the bromodomain inhibitor JQ1, the beta-agonist formoterol, and the p38 inhibitor losmapimod [39][40][41]. Losmapimod was recently tested in a phase 2 clinical trial as a therapeutic for FSHD and showed positive outcomes for secondary and clinical endpoints [15,42]. To determine if secreted ALPP levels as measured by Olink Proteomics assay responded to DUX4 inhibition by these small molecules, we differentiated 1 control and 2 FSHD myoblast cell lines into myotubes for 5 days in the presence of two different concentrations of formoterol, JQ1, or losmapimod.…”
Section: Small Molecule Inhibitors Of Dux4 Suppress Alpp Levelsmentioning
confidence: 99%
“…Since DUX4 protein activates toxic pathways, arguably the most effective DUX4 inhibition strategies will silence DUX4 at the DNA or RNA levels, thereby avoiding protein production. Indeed, several approaches to accomplish DUX4 DNA or mRNA silencing have been previously described, including by our laboratory 16,17 . These strategies, although promising, offer no remedy for inhibiting DUX4 after protein has already been produced.…”
Section: Introductionmentioning
confidence: 99%